PENGEMBANGAN BUKU SAKU BERBASIS KEARIFAN LOKAL SEBAGAI SUMBER BELAJAR PADA MATERI BILANGAN - Harnisa Fitri; Maharani Izzatin; Ferryansyah Ferryansyah (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2019)
This research type was research and development which is conducted at SMP Negeri 8 Tarakan at VII class in Academic Year 2018/2019. The objective of this research was to develop the pocket book based on local wisdom as a learning source on number material that was suitable and practical for the seventh grade students of SMP Negeri 8 Tarakan.The development model used was ADDIE model modification. The ADDIE model consists of five stages that were consisted of: Analysis, Design, Development, and Evaluation. However, because of limitation time and limitation of the research objectives, so the researcher modified the ADDIE model modification by limiting the stage only in development stage. The product testing stage through two stages those were expert assessment and user response. In expert assessment was validated by the material experts, display experts and linguists. In the small group trials was carried out by 2 mathematics teachers and 6 students. On the field trial carried out by 26 students.The result of analysis shows that the product of pocket book based on local wisdom was developed based on validation by the material experts got a very suitable category with the percentage of 85.71%, display experts got a very suitable category with the percentage of 86.25% and linguists got a very suitable category with the percentage of 85 %. Whereas based on the result in the field by the responses of student users got the percentage of 83.5% with a very practical category. Because the pocket book already fulfilled the suitable and practical requirements which consisting of aspects of the content or material feasibility, display feasibility, language feasibility, and practicality of user responses, so pocket book based on local wisdom can be used as a learning source on number material that suitable and practical for seventh grade students of SMP Negeri 8 Tarakan